?-almost statistical convergence of order ? - Çolak, R.; Altin, Y.; Et, M. (Universitatii Al.I.Cuza din Iasi, 2014)
In this paper, we introduce the concept ?-almost statistical convergence of order ?. Also some relations between ?-almost statistical convergence of order ? and strong (formula presented)-almost summability of order  are given. Furthermore some relations between the space (formula presented) and (formula presented) are examined. © Universitatii Al.I.Cuza din Iasi. All rights reserved.
Keywords: Almost convergence; Cesàro summability; Statistical convergence